The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fpsyg.2019.01483
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizations of Addiction and Moral Responsibility

Abstract: The present study explored the connection between conceptualizations of addiction and lay people’s inferences about moral responsibility. In Study 1, we investigated how natural variations in people’s views of addiction were related to judgments of responsibility in a nationwide sample of Norwegian adults. In Study 2, respondents recruited from Mechanical Turk were asked to consider different conceptualizations of addiction and report on how these would affect their judgments of moral responsibility. In Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 57 publications
0
11
0
1
Order By: Relevance
“…The value achieved at the individual level is how they are able to increase self-awareness, responsibility, and relationship skills. According to a recent study, individuals' perceptions of responsibility are crucial in the process of connecting conclusions about causality and control to emotional and behavioral consequences (Rise & Halkjelsvik, 2019). This school-based concept is consistent with the holistic educational framework, which is defined as education that develops all of a student's potential in a balanced manner, including intellectual, emotional, physical, social, and spiritual potential (Musfah, 2012).…”
Section: B Group Intervention School Climate Mediationmentioning
confidence: 90%
“…The value achieved at the individual level is how they are able to increase self-awareness, responsibility, and relationship skills. According to a recent study, individuals' perceptions of responsibility are crucial in the process of connecting conclusions about causality and control to emotional and behavioral consequences (Rise & Halkjelsvik, 2019). This school-based concept is consistent with the holistic educational framework, which is defined as education that develops all of a student's potential in a balanced manner, including intellectual, emotional, physical, social, and spiritual potential (Musfah, 2012).…”
Section: B Group Intervention School Climate Mediationmentioning
confidence: 90%
“…Previous work has shown that a central component of moral responsibility is the agent's ability to choose, which is determined in part by the possession of cognitive and psychological capacities for rational decision-making (Alicke, 2000;Malle, Guglielmo, & Monroe, 2014;Schlenker et al, 1994;Shaver, 1985;Weiner, 1995). Accordingly, lacking autonomous decision-making capacities reduces judgments that an agent is morally responsible (Blakey & Kremsmayer, 2018;Daigle & Demaree-Cotton, 2021;Monroe, Brady & Malle, 2017, Study 4;Rise & Halkjelsvik 2019). Similar patterns are seen in lay judgments of criminal responsibility (e.g.…”
Section: The Role Of Autonomous Consent In Moral Cognitionmentioning
confidence: 91%
“…http://www.drpaulwong.com/what-is-the-greatest-need-today-responsibility-isthe-key-to-surviving-and-thriving-in-dangerous-times / Both research and clinical evidence support his view (e.g., Wong, 2010Wong, , 2012. The corollary is also true -the lack of responsibility may lead to addiction (e.g., Rise & Halkjelsvik, 2019;Wong et al, 2013) and crimes (Trivedi-Bateman, 2020). Given the important role of responsibility in wellbeing and health, the main aim of the present paper is to validate the responsibility measure based on the Responsibility Checklist originally published in Wong (2019b).…”
Section: Table 1 Wong's Responsibility Manifestomentioning
confidence: 99%